Study of Adoption of New Technologies for Furthering Biodiversity Conservation Commerce and Trade of Medicinal and Aromatic Plants of India - Ramesh Singh, D. R. (Indian Forester, 2005)
MAPs provide a diversification and crop intensification option both to farmers and foresters. Organic farming or forest production can be introduced if returns on investment are remunerative. Biodiversity conservation can be enhanced by providing better access to these reinvented practices eg., organic farming. Traditional knowledge available regarding distribution, varieties, collection and processing has to be integrated with scientific and technological inputs. Breeding for higher quality and quantity in a short period is a distinct possibility both by traditional and modern practices. Central to the exercisc of diversification and intensification option is sustained demand by domestic and international markets. Quality control has to he upgradcd in all respects to lay claim to the rightful share in international market in consonance with the knowledgc and techniques prescribed by Atharvaveda. Association of ncutraceuticals with virility promoting herbal drugs currently in grcatcr dcmand is likely to become unsustainable in the long run. This narrowly focused approach has to be combined with a stronger focus on preventive and curative aspects of medicinal plants to serve the larger public need of safc and efficacious herbal health care system. Market intelligence of total international demand and present levels of wild and domesticated supplies along with prices of planting stock and different grades of produce need to be made available to prospedive farmers to prevent tradc cycles. The search for the mythical ’sanjivini buti’ is to be startcd in all sincerity as a national goal for serving ’vasudaivakutumb acam’ of the community of nations.